First Report of Fusarium oxysporum f. sp. lycopersici Race 2 on Tomato in Italy - Stravato, V M (Plant disease, 1999)
During the summer of 1997, symptoms of Fusarium wilt were observed on tomato (Lycopersicon esculentum Mill.) cvs. Monica F1 and PS 110, which bear the I gene for resistance to race 1 of Fusarium oxysporum Schlechtend.:Fr. f. sp. lycopersici (Sacc.) W.C. Snyder & H.N. Hans., in two commercial production greenhouses in Latium (Fondi) and one greenhouse in Sardinia (Oristano). Infected plants showed yellowing, stunting, vascular discoloration, and premature death. A fungus from tomato stems with discolored vascular tissue was consistently isolated on potato dextrose agar (PDA) and, based on morphological features, was identified as F. oxysporum. To verify the pathogenicity of four fungal isolates, cv. Bonny Best tomato plants, which do not carry genes for Fusarium wilt resistance, were inoculated by dipping roots of 2-week-old seedlings in a suspension of 105 microconidia per ml for 30 s. Inocula were obtained from 1-week-old fungal cultures grown on PDA. Roots of control plants were dipped in water. Seedlings were transplanted to pots containing peat and river sand (1:1, vol/vol) and placed in a greenhouse at 20 to 25°C. One month after inoculation, all fungal isolates provoked wilting of inoculated plants. No symptoms were observed on control plants. The morphological features of the fungus reisolated from diseased plants were similar to those of the original isolates. Based on the pathogenicity test, we concluded that the fungal isolates belong to F. oxysporum f. sp. lycopersici. To determine the races of the fungal isolates, differential tomato lines VFN8 (I gene for resistance to race 1), Florida MH-1 (I and I2 genes for resistance to races 1 and 2), and I3R (I, I2, and I3 genes for resistance to races 1, 2, and 3) were inoculated with the four fungal isolates, using the same procedure described for the pathogenicity test. Because disease symptoms were detected on VFN8 but not on Florida MH-1 and I3R, we deduced that the fungal isolates belong to F. oxysporum race 2. This is the first report of F. oxysporum f. sp. lycopersici race 2 in Italy. Previous research indicated that race 1 is present in Italy (1). Currently, many commercially acceptable cultivars resistant to races 1 and 2 are available to Italian greenhouse growers. Reference: (1) M. Cirulli. Phytopathol. Mediterr. 4:63, 1965